Del cinismo helénico y el nuestro - Piovano, Ana Laura (2015)
Si de elucubrar un saber respecto de la práctica se trata, sostenemos como condición de posibilidad para hacerlo el esfuerzo por estar a la altura de la subjetividad de nuestra época. La represión no alcanza a dar cuenta del malestar en la cultura en el capitalismo de consumo actual. Nos interesa situar en la hipermodernidad el rasgo de cinismo, de desprecio por el Otro, de denuncia al semblante, en tanto que obstáculo para nuestra intervención. Habiendo situado ya la posición cínica como una más de las respuestas posibles frente al trauma, en esta ocasión, abordaremos su manifestación actual en su diferencia radical con la otrora Escuela filosófica griega. Para el abordaje del cinismo antiguo realizamos una indagación bibliográfica que privilegia "Vidas y anécdotas de los filósofos cínicos" de Diógenes Laercio incluida en "La secta del perro" de Carlos García Gual. En tanto, para efectuar el contrapunto con el cinismo actual nos serviremos de la tesis doctoral de Peter Sloterdijk "Crítica de la razón cínica" de 1984 y del más reciente "Cinismos" del polémico filósofo francés Michel Onfray. (Resumen parcial)
When it comes to devising knowledge regarding practice, we hold as a condition of possibility for the making the effort to be up to scratch with the subjectivity of our times. Repression fails to take into account the "cultural malaise" in the present consumer capitalism. We are interested in locating the trait of cynicism, of contempt for the Other, in 'hyper modernism'. At this point it articulates around consumption. There, where there was an ideal the "object a" unveiled takes its place. Addictions are multiplied: gambling -to legal or illegal substances- to food, to work. The subject, in a sort of extended bulimia, endlessly consumes, is sickened, vomits, and is empty. In his "Proposition of 9 October 1967 " Lacan said " Our future as common markets will find its equilibrium in a harsher extension of the processes of segregation". Segregation establishes itself in the unmistakable social manifestation of a time when what is different is annihilated, reduced to scrap. The pathologies that we encounter in the different areas where we practice psychoanalysis are not so much neurotic but the ones that are born of the impulse to the whole. (Partial abstract)
Keywords: Psicoanálisis; Sufrimiento; Psíquico; Emergencia; Social; Intervenciones clínicas; Psychoanalysis; Psychic suffrering; Social emergency; Symbolization